History and historical DNA: Identity of Chelodina intergularis Fry, 1915 and type localities of C. intergularis and C. rugosa Ogilby, 1890 - Kehlmaier, Christian; Kuchling, Gerald; Shea, Glenn; Georges, Arthur; Zhang, Xiuwen; Fritz, Uwe; Thomson, Scott (Zootaxa, 2024)
Based on the phylogenetic placement of a near-complete mitogenome sequence of the holotype of Chelodina intergularis Fry, 1915 generated with hDNA approaches, we present evidence for the synonymy of this nominal species with Chelodina rugosa Ogilby, 1890. The type specimens of both taxa are housed in the Australian Museum, Sydney. Scrutinizing historical records, we conclude that the type locality of both taxa is most likely the vicinity of Somerset, at the northern extremity of Cape York Peninsula, Queensland, Australia. We figure and describe both type specimens. Our results support the earlier conclusion that the exceptional arrangement of intergular and gular scutes in the holotype of C. intergularis is an individual aberration.